PRODUCT DEVELOPMENT TO INCREASE CONSUMER BUYING INTEREST BASED ON CONSUMER REFERENCES (Batik Industry Center Masaran Sragen) - Pratiwi, Adcharina; Murti, Fadjar Hari; Marimin, Agus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Product development research, aims to identify and analyze the attributes of batik fabric products developed and expected consumer desires based on marketingmix. The results of the research as input for product development for batik MSMEs, development of the attributes of batik fabric products of interest to consumers. The research used an exploratory method through a sample of 100 consumers who had purchased batik fabric products at the Masaran Sragen batik MSMEs. Data collection methods are through questionnaires, interviews to respondents and surveys, interviews, direct observation with MSMEs. Data analysis uses conjoint and Structural Equation Modeling (SEM) analysis. Based on the analysis that batik fabric products are in demand by consumers characterized by: (1) product variables: (a) fabric material made of cotton fabric; (b) features modern-traditional combination motifs; (c) fabric size 110 cm x 240 cm; (d) combination batik, written and stamped; (2) price variables: (a) selling price between Rp. 150,000, - to Rp. 200. 000 per piece; (b) cash payment system; (c) giving discounts when purchasing; (3) promotion variables: (a) advertisements on social media/internet, marketing personnel and signboards; (b) sold in stores/boutiques and online shops; (c) actively participating in events; (4) distribution variables; (a) sold in stores in all districts/cities in Indonesia; (b) timely delivery; (c) sales through stores and online. Keywords: development, product, batik, interest, purchasing, consumers.